Defect distribution and microstructure heterogeneity effects on fracture resistance and fatigue behavior of EBM Ti–6Al–4V. (January 2017) - Seifi, Mohsen; Salem, Ayman; Satko, Daniel; Shaffer, Joshua; Lewandowski, John J.
Highlights: Comparison of fracture toughness and fatigue crack growth behavior of as-deposited vs HIP EBM Ti-6Al-4V. Microstructure (large scale EBSD) and defect (via tomography) characterization of as-deposited vs HIP EBM Ti-6Al-4V. Orientation-, location-, and process (as-deposited vs. HIP)- dependence of properties related to microstructure and/or defect characterization. Comparison of microstructure/properties obtained on the different generation of EBM machines. Use of materials informatics techniques to correlate structure/property relationships. Abstract: Recent work has documented orientation-dependent fracture and fatigue properties of as-deposited Ti–6Al–4V manufactured by electron beam melting, in addition to providing a modified ASTM nomenclature to begin the discussion of possible orientations to consider for mechanical characterization. In this work, the role of location-specific defect distribution and microstructure variation on fracture resistance of Ti–6Al–4V produced via different generation of Arcam machines (e.g. A2, A2X) is reported, along with the effects of subsequent hot isostatic pressing (HIP) treatments. Microstructure informatics of measured EBSD of α phase, reconstructed EBSD data for β phase, defect distributions from μCT scans, and fracture surface morphologies were used to establish correlations between microstructure and mechanical performance. In the fatigue crack growth tests, the fatigue threshold, Paris law slope, and stress intensity at overload were determined at various load ratios while fatigue precracked samples were also tested to determine the fracture toughness using an R -curve approach since samples were not thick enough for valid plane strain K IC . Distinct differences in both the magnitude of toughness and crack growth resistance behavior were documented for the as-deposited and HIP samples. Fracture surface examination and μCT scans revealed lack of fusion defects, disbonded regions, and random/isolated porosity for the as-deposited samples tested in this study. However, the resulting fracture/fatigue properties were in the range of those reported for the cast and wrought Ti–6Al–4V. HIPping eliminated the porosity/defects but HIPped samples exhibited coarsening of the α laths and changes to the magnitude of toughness and crack growth resistance.